EXPERIMENTAL INVESTIGATION ON THE ROLE OF THERMO-ACOUSTICS ON SOOT FORMATION - Ravichandran, Rahul Ravi; Dash, Sambit Supriya; Malhotra, Vinayak (International Journal of Research -GRANTHAALAYAH, 2018)
Combustion is a complex phenomenon that involves the interaction of multiple phenomena, the cumulative effect of which give rise to the common flame that comprises wide range of practical, functional to propulsion applications. An interesting aspect that needs attention is the effect of the various surrounding environment phenomenon on its behavior and properties of premixed flames. It is noteworthy that soot formation is the main cause of pollution and a major cause of inefficiency of current propulsion systems. These phenomena root variety of energy interactions leading to energy transformations which in turn affect the flame behavior. Present work focuses on experimental investigations and implications of the externally induced acoustics on partially premixed flames. The subject is extensively studied as thermo-acoustics, and the current work emphases on studying its role on soot formation on premixed flames. Experimentation was carried out on a scaled setup comprising of a butane cylinder fitted with a nozzle, that houses 3 arrays consisting of 4 holes each placed equidistant to each other for entraining air. The resulting flame is impinged with acoustics from two independent and similar sources placed equidistant from the center of the nozzle. The entire process is systematically video graphed using a 60-fps regular CCD and analyzed for variation in flame heights and flickering frequencies. The observations involve fixed fuel mass flow rate with varying configuration of entrainment holes and acoustic frequency under normal ambient atmospheric conditions. The work establishes significant outcomes on the effect of acoustics on soot formation. The results are likely to encourage better understanding with applicability to commercial and domestic utilizations for energy generation for enhanced effectiveness and reduced hazards.